UPAYA PENINGKATAN NILAI KALOR BATUBARA SUB BITUMINUS MELALUI PENURUNAN KADAR LENGAS (MOISTURE) MENGGUNAKAN OVEN CONVEYOR SEBELUM DITERIMA OLEH KONSUMEN - Thoufiq Ridhowan Thoufiq; Fadarina HC; Muhammad Taufik (KINETIKA, 2022)
Coal with a high moisture content and low calorific value is usually classified as low rank coal. Improving the quality of coal can be done by reducing the water content which will increase the calorific value. The technology used to improve the quality of coal, one of which is using a conveyor oven before the coal is received by consumers or used by the industry. The amount of water that evaporates can be influenced by the length of the conveyor, the speed of the conveyor and the temperature used. The experiment was carried out on a laboratory scale using samples of coal that were dried in a rack-type oven that had been modified to resemble a conveyor oven. Furthermore, the coal samples were analyzed for Total Moisture and Calorific Value. Optimal drying on a laboratory scale to obtain a total water reduction of 2.2% (Ar) and an increase in heating value of 179 Cal/g (Ar) is at a drying temperature of 270 ℃ for 90 seconds. Key words : Coal Drying, Conveyor Oven, Total Moisture, Calorific Value